EFFECT OF DIFFERENT TEMPERATURE ON GROWTH RATE AND SURVIVAL BETTA FISH FRY (Betta splendens) - Permata Sari, Agun; Cokrowati, Nunik; Marzuki, Muhammad (Jurnal Media Akuakultur Indonesia, 2022)
Betta splendens is an ornamental fish with a beauty appeal to the shape of the tail fin and color. The purpose of this study was to determine the effect of different temperatures and optimal temperatures on the growth rate and survival of betta fish fry (Betta splendens). The research method was experimental using a completely randomized design (CRD). With 4 treatments, namely P1 (control), P2 (25°C), P3 (27°C), P4 (29°C). The result of the highest specific weight growth rate was in treatment P4 (4.08 g), the lowest treatment was in treatment P2 (3.85 g). The highest specific length growth rate was in treatment P4 (1.78 cm), the lowest treatment was at P2 (1.52 cm). The highest feed conversion ratio (FCR) was in treatment P2 (5.82%), the lowest FCR value was in treatment P4 (6.23%). The survival rate of the highest Betta splendes fry was on average 100% in the P1, P3, and P4 treatments. The survival value of betta fish fry was lowest in treatment P2 (82%). The results of water quality parameters for P1 treatment temperature ranged from 27-28.2°C, pH ranged from 6.3-7.85, dissolved oxygen ranged from 6-8.8. The results of the analysis of variance test (Anova) on the growth of the specific weight of betta fry produced F-count -30.85 > F-table 5% (4.07). Specific length growth resulted in an F-count value of 2.75 < F-table 5% (4.07). Feed conversion ratio (FCR) F-count 1.24 < F-table 5% (4.07). The survival of betta fish fry resulted in F-count 12.60 > F-table 5% (4.07). The conclusion of the study is that temperature has a significant effect on the growth rate and survival of Betta splendens fry. The optimal temperature for growth rate was obtained in treatment P4 (29°C) of 4.08 g, optimal survival rate was obtained in treatments P1 (control), P3 (27°C), and P4 (29°C).